Detection and Estimation of Heavy Metals in Broiler Meat Available in Lahore, Pakistan - Salamat, Hira; Shahbaz, Sana (BioScientific Review, 2022)
Cadmium (Cd) and lead (Pb) are toxic environmental pollutants. These heavy metals create serious health issues in consumers. The current study aimed to identify the quantity of lead and cadmium in broiler chicken, including in its liver and kidneys, since the demand for chicken meat as a food source is increasing day by day. Forty (40) broiler chickens were purchased from the various markets of Lahore, Pakistan including the markets of Sadar Cantt area, Shahdra, Alkarim park, Anarkali, and Muslim town. These chickens were collected, processed, and analyzed to determine the levels of lead and cadmium in their internal organs (liver and kidneys) using atomic absorption spectrophotometer. This process was carried out in the laboratory of PCSIR after the digestion of all samples via nitric acid (HNOз) and hydrogen peroxide using the wet digestion method. The range of the mean concentration of lead (4.50 - 8.50ug /g) and cadmium (25.00 - 27.75 ug/g) in the internal organs of broiler chicken exceeded the permissible level of 0.05% recommended by the World Health Organization (WHO). ANOVA analysis revealed that the presence of heavy metals was not significant in the internal organs of broiler meat collected from different areas of Lahore, since the p-value was greater than the significance level (p > 0.05). Hence, heavy metal concentrations were recorded as above the permissible level recommended by the WHO.